The Nonspread of Innovations: the Mediating Role of Professionals - Ferlie, Ewan; Fitzgerald, Louise; Wood, Martin; Hawkins, Chris (Academy of Management Journal, 2005)
Two qualitative studies in the U.K. health care sector trace eight purposefully selected innovations. Complex, contested, and nonlinear innovation careers emerged. Developing the nonlinear perspective on innovation spread further, we theorize that multi-professionalization shapes “nonspread.” Social and cognitive boundaries between different professions retard spread, as individual professionals operate within unidisciplinary communities of practice. This new theory helps explain barriers to the spread of innovation in multiprofessional organizations in both health care and other settings.